Generative AI for growth hacking - Rezazadeh, Arash (2025)
Rezazadeh, A., Kohns, M., Bohnsack, R., António, N., & Rita, P. (2025). Generative AI for growth hacking: How startups use generative AI in their growth strategies. Journal of Business Research, 192, 1-16. Article 115320. https://doi.org/10.1016/j.jbusres.2025.115320 --- %ABS3% --- Rene Bohnsack and Arash Rezazadeh were supported by funds through European Union’s Horizon projects: OMEGA-X (Grant agreement ID: 101069287; DOI: 10.3030/101069287) and exPEDite (Grant agreement ID: 101139527; DOI: 10.3030/101139527). Nuno António and Paulo Rita were supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS) (https://doi.org/10.54499/UIDB/04152/2020).